2002
DOI: 10.1006/viro.2001.1342
|View full text |Cite
|
Sign up to set email alerts
|

All Four Sendai Virus C Proteins Bind Stat1, but only the Larger Forms also Induce Its Mono-ubiquitination and Degradation

Abstract: Sendai virus infection strongly induces interferon (IFN) production and has recently been shown to interdict the subsequent IFN signaling through the Jak/Stat pathway. This anti-IFN activity of SeV is due to its "C" proteins, a nested set of four proteins (C', C, Y1, Y2) that carry out a nested set of functions in countering the innate immune response. We previously reported that all four C proteins interact with Stat1 to prevent IFN signaling through the Jak/Stat pathway. Nevertheless, only the longer C prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 43 publications
4
111
1
Order By: Relevance
“…In particular, all four have been shown to interact with Stat1, an interaction that blocks type 1 interferon signaling to reporter genes carrying interferon-stimulated response elements. However, whereas binding to either CЈ or C leads to proteasomemediated Stat1 turnover and hence a subsequent block on the interferon-induced antiviral state, binding to the Y proteins does not destabilize Stat1, and the antiviral state can be observed (36,45). Our own work suggests that both CЈ and C expression but not Y is detrimental to cell viability.…”
Section: Y Protein Expression: Initiation Versus Proteolytic Processimentioning
confidence: 74%
See 3 more Smart Citations
“…In particular, all four have been shown to interact with Stat1, an interaction that blocks type 1 interferon signaling to reporter genes carrying interferon-stimulated response elements. However, whereas binding to either CЈ or C leads to proteasomemediated Stat1 turnover and hence a subsequent block on the interferon-induced antiviral state, binding to the Y proteins does not destabilize Stat1, and the antiviral state can be observed (36,45). Our own work suggests that both CЈ and C expression but not Y is detrimental to cell viability.…”
Section: Y Protein Expression: Initiation Versus Proteolytic Processimentioning
confidence: 74%
“…6A), and assays have yet to discern a clear functional difference between the two. Both inhibit viral genome expression (7,8) and bind Stat1 to induce its turnover (10,36). However, we reasoned that the additional amino acids on CЈ may serve as a targeting signal that could direct at least a fraction of the protein to a particular cellular location.…”
Section: Y Protein Expression In Vitro Ismentioning
confidence: 99%
See 2 more Smart Citations
“…While intranuclear functions of other paramyxovirus M proteins have not been described, recent characterization of the interactome of the NiV, HeV, SeV and NDV M proteins (Pentecost et al, 2015) identified a number of nuclear proteins, suggesting that M proteins may have several roles in the nucleus, which the new proteomic data should help to elucidate. (Garcin et al, 2002) *Excludes components of the nuclear transport machinery (see Table 2 …”
Section: Mevmentioning
confidence: 99%